ZAKAT DI MALAYSIA DALAM PERSPEKTIF EKONOMI - Nurhasanah, Nurhasanah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
Zakâh is the implications of the high level of practice Muslims toward the teachings of Islam in Malaysia. It has been carried out since the pre-colonial, colonial times, post-independence, 1957, 80s, and 90s to the present. Regulatory changes are not necessarily set zakat source in accordance with the economic development and professional management. In zakâh  management, government noted that the potential fellowship zakâh increased in accordance with the economic progress of the Muslim community. To foster public confidence in the management of zakâh, government through the Majelis Islam Wilayah  Persekutuan (MAIWIP) established the Center levy zakâh (PPZ) in 1991 in order to create a professional zakâh management by implementing corporate systems.DOI: 10.15408/aiq.v4i1.2540